An analysis of business administration use of the Piła City Card as a means of urban communication - Gorzelańczyk, Piotr; Jarka, Zofia; Pachowicz, Tomasz; Kalina, Tomáš; Jurkovič, Martin (Analiza business administration wykorzystania Pilskiej Karty Miejskiej w środkach komunikacji miejskiej w Pile)
The article will present the application and use of the Piła City Card (PCC) which is utilized as a ticket in public transport in Piła (MZK). In the next stage of research, other possibilities of its use will be presented. The aim of the study was to analyse the existing system of how the PCC works and to get to know the public opinion on the subject of its functioning and how to further expand its use. The research was carried out in the city of Piła, using a questionnaire consisting of 12 single-choice closed and 2 open questions. The residents of the City of Piła were satisfied with the services provided by MZK and the introduction of an electronic ticket encoded on the PCC. The functioning of this card makes travelling much easier. The respondents also gave many interesting suggestions regarding other applications of the PCC than just in communication. Some of the proposals, after consultations with the city authorities and MZK, are currently being implemented
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 1, s. 28-45